Peran Digitalisasi Terhadap Pembangunan Pertanian dalam Rangka Mewujudkan Ketahanan Pangan - Yudhistira Bagas Anggoro; Didit Purnomo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to determine the impact of digitalization in the form of internet usage, computer usage, and E-commerce on agricultural production, specifically rice production in Indonesia. The data used are secondary data from 34 provinces in Indonesia for the period 2020 to 2023. This study uses the panel data linear regression analysis method with the E-views 12 application to process the data. The dependent variable used is the amount of rice production, while the independent variables include the number of internet users, the number of computer users, and e-commerce in the agricultural sector. The research results show that internet usage and computer usage significantly affect rice production in Indonesia. Meanwhile, e-commerce in the agricultural sector does not significantly affect rice production in Indonesia. The government needs to continue supporting the development of digitalization as one of the efforts to encourage the growth of rice production in Indonesia.